Gender‐Role Attitudes Among Immigrant Latinas: Empowering Women. Issue 4 (22nd November 2018) - Villalba, Karina; Ramirez‐Ortiz, Daisy; Dévieux, Jessy G.; Attonito, Jennifer; Rojas, Patria
Abstract : In general Latinos hold more conservative attitudes regarding gender roles when compared to Whites. However, Latinos born in the United States with higher education are more likely to have egalitarian gender role attitudes compared to Latino immigrants. The aim of this study was to analyze the relationship between gender role attitudes and acculturation, marianismo, and relationship control, among Latina immigrants living in the United States. A hierarchical regression and correlation analysis were used to measure the outcome of this study. A total of 234 women were included in the study with a mean age of 34 years old. The education level was less than high school (53 percent), with the majority employed (54 percent). The average time living in the United States was 8 years (SD = 2.0). Acculturation, marianismo, and relationship control were significantly associated with gender‐role, R 2  = .207, F (3, 95) = 11.3, p  = 0.001. The correlation analysis showed an inverse relationship between egalitarian attitudes and marianismo (r = −.304, p  < .0005) and a positive relationship with acculturation (r = .295, p  < .0005). Egalitarian gender role attitudes were observed with an inverse bidirectional relationship between marianismo and acculturation among Latino immigrant women living in the United States.